KUALITAS PELAYANAN DALAM PENGURUSAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DAN KARTU KELUARGA (KK) DI DISDUKCAPIL KABUPATEN BUOL - Mahmud, Syamsiar I.; Alhamid; Mutmainah, Riski (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2022)
Public service is a problem that is still an interesting issue, because until now the bureaucracy has not been able to provide quality services to the community as service recipients, this is because the service process is still convoluted, the bureaucratic flow is still rigid and unable to provide guarantees for certainty of service time, limited human resources and facilities and infrastructure make the quality of service for the management of E-KTP and KK at the Civil Registry Office of Buol Regency still not optimal. The purpose of conducting the research was to find out and describe the quality of service for managing E-KTP and KK at the Dukcapil Distric of Buol Regency. The research method used is descriptive qualitative, because it wants to reveal how the service quality of E-KTP and KK management at the Dukcapil Distric of Buol Regency. The research location was the Dukcapil Distric of Buol Regency, the data analysis technique used Milles and Huberman. The results showed that the service quality of E-KTP and KK arrangements at the Civil Registry Office of Buol Regency, seen from the aspects of tangibles (direct evidence), reliability (reliability), the level of human resources was still limited to responsiveness, assurance, and empathy. optimal, because it still has limited facilities (buildings) and infrastructure, the condition of the service room is narrow, because the Dis Dukcapil building manages KTP and KK so that it is unable to accommodate the number of people, the service staff is relatively slow in providing services, the service officers are not friendly in providing services. Discrepancies in the time/hours of service officers in providing services; and most consumers do not feel any special attention from service officers to consumers.